2021
DOI: 10.1021/acs.jpcb.1c01281
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Interactions of α-Synuclein Revealed by Multiscale Molecular Dynamics Simulations, Markov State Models, and NMR

Abstract: α-Synuclein (αS) is a presynaptic protein that binds to cell membranes and is linked to Parkinson’s disease (PD). Binding of αS to membranes is a likely first step in the molecular pathophysiology of PD. The αS molecule can adopt multiple conformations, being largely disordered in water, adopting a β-sheet conformation when present in amyloid fibrils, and forming a dynamic multiplicity of α-helical conformations when bound to lipid bilayers and related membrane-mimetic surfaces. Multiscale molecular dynamics s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 92 publications
0
15
0
Order By: Relevance
“…On the other hand, the structured monomer entries still contribute to the off-pathway target criterion because they are distinct from the simulated monomer ensemble. These monomer PDB entries are partly structured (containing α-helices) by binding to micelles (e.g., PDB codes 2KKW and 1XQ8) and are thought to be involved in various aspects of α-synuclein physiology. Thus, membrane-bound PDB monomer structures are treated separately from the unstructured isolated monomer ensemble.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the structured monomer entries still contribute to the off-pathway target criterion because they are distinct from the simulated monomer ensemble. These monomer PDB entries are partly structured (containing α-helices) by binding to micelles (e.g., PDB codes 2KKW and 1XQ8) and are thought to be involved in various aspects of α-synuclein physiology. Thus, membrane-bound PDB monomer structures are treated separately from the unstructured isolated monomer ensemble.…”
Section: Resultsmentioning
confidence: 99%
“…The region between residues 30–100 is, on the contrary, slightly positively charged with 9 positive and 6 negative charges . Sansom and collaborators have suggested that the majority of the contacts between α-synuclein and an anionic lipid bilayer involve the N-terminal helix and interhelical loop regions. Also, they observed that α-synuclein monomer interactions with DOPE and DOPS are preferred to those with DOPC.…”
Section: Resultsmentioning
confidence: 99%
“…The membrane interaction of α-Syn is a classic topic related to Parkinson’s disease, and many experimental and simulation studies have been carried out on this topic. Using MD simulations, important physical insights have been revealed to understand the membrane binding process of α-Syn, ,, the effects of membrane component and curvature, , the structure and aggregation of α-Syn, , etc. However, the correlation between cholesterol and the membrane binding of α-Syn remains unclear, even though the effect of cholesterol on membrane properties has been well studied. Thus, in this work, we aimed to bridge cholesterol and the membrane binding of α-Syn, by scrutinizing the binding process and the structural characteristics of membrane-bound α-Syn.…”
Section: Discussionmentioning
confidence: 99%
“…The CHARMM36m force field was used to describe our models, and the TIP3P water model was adopted. The CHARMM36m force field has been widely used in MD simulation studies of biological systems, and it is suitable for aqueous solvation systems of lipids and proteins. ,, All of the MD simulations were performed using the GROMACS 2019.6 () package . The CHARMM-GUI Membrane Builder online service was used to generate lipid bilayer models.…”
Section: Models and Simulation Methodsmentioning
confidence: 99%